Gaming the system: Stimulating rules and behavior change for governance of groundwater and conjunctive use in India - Meinzen-Dick, Ruth S.; Falk, Thomas; Priyadarshini, Pratiti; Singh, Subrata; Mittal, Rajesh (2021)
Prepared by: Ruth Meinzen-Dick, Thomas Falk, Pratiti Priyadarshini, Subrata Singh, Rajesh Mittal